DLforum – A multidisciplinary online discussion forum for data linkage researchers and practitioners: https://dmm.anu.edu.au/DLforum/ - Christen, Peter; Ranbaduge, Thilina; Vatsalan, Dinusha (International Journal of Population Data Science, 2018)
Data linkage, the process of identifying records that refer to the same entities across databases, is a crucial component of Population Data Science. Data linkage has a history going back over fifty years with many different methods and techniques being developed in various disciplines including computer science, statistics, and health informatics. Data linkage researchers and practitioners are commonly only familiar with methods and techniques that have been developed or are used in their own discipline, and they often only follow research that is being published at venues in their own discipline. There is currently no single online resource that allows data linkage researchers and practitioners across different disciplines to exchange ideas, post questions, or advertise new publications, software, open positions, or upcoming conferences and workshops. This leads to a communication gap in the multi-disciplinary field of data linkage. We aim to address this gap with the DLforum, a public online discussion forum for data linkage. DLforum contains several discussion areas, including publication announcements, resources (software and data sets), information about upcoming conferences and workshops, job opportunities, and general questions related to data linkage. The forum includes a moderation process where all registered users can post content and reply to posts by other users. We anticipate that the number of users registered and the amount of content posted in the forum will show that such an online forum is of value to data linkage researchers and practitioners from different disciplines to effectively communicate and exchange their knowledge, and thus form an online community of practice. In this paper we describe the methods of developing the DLforum, its structure and content, and our plan on how to evaluate the forum. The DLforum is freely available at: https://dmm.anu.edu.au/DLforum/